Pengaruh Metode Pembelajaran Inkuiri Terbimbing Terhadap Hasil Belajar Peserta Didik Pada Pelajaran IPA Kelas V SD Islam Khalifah Palu - Nurul Hikmah Ramadani; Rustina Rustina; Arda Arda (Koordinat Jurnal MIPA, 2021)
This research aims to determine the effect of guided inquiry learning methods on student learning outcomes in science lessons. This research is quantitative study. Sample of this research were 34 students of fifth grade SD Islam Khalifah Palu. The research instrument was a multiple choice question. The data analysis was done in the form of a validity test with SPSS 23 and a reliability test with KR 21. Hypothesis testing was done by using the One Sample T-Test with SPSS 23. The results of the tests were obtained ttest of 2.149 and Sig. (2-tailed) 0.039. Based on this value, it can be concluded that the research hypothesis (H1) is accepted. The average value of students after learning with the guided inquiry method is greater than the KKM. The results of these studies indicate that the guided inquiry learning method has a significant positive effect on student learning outcomes.